Remote Supratentorial Recurrent Medulloblastoma: Case Study and Literature Review - Dominari, Asimina; Antoniades, Elias; Capiccelo, Antonio; Hatzipantelis, Emmanuil; Foroglou, Nikolaos (Asian Journal of Neurosurgery, 2022)
Medulloblastomas comprise 10% of pediatric brain tumors. Subfrontal recurrence is uncommon and has been associated with prone positioning, inadequate irradiation of the cribriform plate area, and hydrocephalus management. We discuss the case report of an 8-year-old boy with subfrontal medulloblastoma recurrence. The literature was reviewed using terms such as “medulloblastoma,” “subfrontal recurrence,” and “child.” Forty-eight cases of subfrontal medulloblastoma recurrence were identified. The mean age at presentation was 12.3 years. Gross total resection was achieved in 44%, most patients received adjuvant radiation therapy, and approximately 25% received chemotherapy. The mean recurrence interval was 2.6 years. The mean number of recurrences per patient was 1.2 and the mean survival period was 3.3 years. Even in the case of meticulous resection and sufficient irradiation, recurrences may still occur. Our case indicates that resection of the recurrent lesion and repeat irradiation may benefit patients with satisfactory short-term results.
Keywords: subfrontal; recurrence; medulloblastoma; child; predisposing factors; treatment